Time analysis for the IAAF World Championships London 2017 5000 m Men's - Hanley, B.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s 5000 m final was held on the evening of August 12th. The average speeds for each of the top eight athletes over every 400 m segment (and last 200 m) are included in this report, as well as a graph of each of these athletes` positions at each 400 m split (and last 200 m). The split data were provided by SEIKO. The results of the final are shown. (Attention! registration on the IAAF site is required for downloading)